Existence of Positive, Negative, and Sign-Changing Solutions to Discrete Boundary Value Problems. (10th March 2011) - Zheng, Bo; Xiao, Huafeng; Shi, Haiping
Abstract : By using critical point theory, Lyapunov-Schmidt reduction method, and characterization of the Brouwer degree of critical points, sufficient conditions to guarantee the existence of five or six solutions together with their sign properties to discrete second-order two-point boundary value problem are obtained. An example is also given to demonstrate our main result.